Murder your employer ebook The mcmasters guide to homicide. - Holmes, Rupert (2023)
A New York Times bestseller! From Edgar Award–winning novelist, playwright, and story-songwriter Rupert Holmes comes a diabolical thriller with a killer concept: The McMasters Conservatory for the Applied Arts, "a fantasy academy laid out like a combination of Hogwarts, Downton Abbey, and a White Lotus –style resort" ( Los Angeles Times ) dedicated to the art of murder where students study how best to "delete" their most deserving victim. Who hasn't wondered for a split second what the world would be like if a person who is the object of your affliction ceased to exist? But then you've probably never heard of The McMasters Conservatory, dedicated to the consummate execution of the homicidal arts. To gain admission, a student must have an ethical reason for erasing someone who deeply deserves a fate no worse (nor better) than death. The campus of this "Poison Ivy League" college—its location unknown to even those who study there—is where you might find yourself the practice target of a classmate...and where one's mandatory graduation thesis is getting away with the perfect murder of someone whose death will make the world a much better place to live. Prepare for an education you'll never forget. A "fiendishly funny" ( Booklist ) mix of witty wordplay, breathtaking twists and genuine intrigue, Murder Your Employer will gain you admission into a wholly original world, cocooned within the most entertaining book about well-intentioned would-be murderers you'll ever read.